Challenges in applying theoretical knowledge from the general medicine course in clinical practice: A qualitative study - Milad Safari; Shahrzad Shahidi; Maryam Avizhgan (Zanjan University of Medical Sciences and Health Services, 2024)
Background & Objective: Clinical education stands as a critical domain for enhancing clinical skills. Evolving global demands, marked by an information explosion and dynamic shifts in disease patterns, coupled with deficiencies in clinical training and its disconnect from theoretical knowledge, pose significant challenges in patient care. This study aims to explore the obstacles and challenges associated with applying theoretical knowledge from the general medicine course in clinical practice. Materials & Methods: This qualitative research employed a conventional content analysis approach. Twenty participants, each with a minimum of one year of clinical education experience, were purposefully selected to ensure maximum diversity. Data were collected and analyzed through individual semi-structured interviews. Results: The data analysis identified five main categories as the primary challenges in applying theoretical knowledge in the clinical environment. These include "weakness of inputs," "weakness of policy," "ineffective training and novice practitioners," "ethical lapses, unprofessional conduct," and "challenges while studying." Additionally, 14 subcategories were derived, collectively representing the main challenges faced. Conclusion: The application of theoretical knowledge acquired in various aspects of clinical education is hampered by diverse challenges. These challenges manifest at different levels, encompassing management, policy, infrastructure, and human and material resources. Prioritizing identified issues and implementing corrective actions based on existing capacities is the initial step in overcoming these challenges.